APPLICATION OF NEW STUDENT REGISTRATION BASED ON MOBILE AT SMK SINAR HUSNI MEDAN - Muhamad Alda; Afifudin Afifudin (LPPM Nusa Mandiri, 2020)
SMK Sinar Husni still uses the manual method of registering new students, resulting in several problems or obstacles. Problems encountered include, prospective students need time, energy and large costs in the registration process because prospective students must come directly to the school to see registration information and fill out the registration form, the administration process of admission of new students tends to be slow, because there is prospective student data those who have registered have not been integrated and managed well, making reports of prospective students who register takes quite a long time, and the work process becomes slower and there are frequent errors and repetitions in making the report and still use the archives in physical form so that they are vulnerable to damage or even missing. This research, the author uses the experimental method, the authors build a new student registration application based on Android mobile. The purpose of this research is to build an Android-based mobile application that can be used by prospective students in registering and can help the Sinar Husni Vocational School in processing data registration of new students and the process of making reports of prospective students. The application is designed and built using the waterfall model, so that each research activity is based on the stages contained in the waterfall model. The application is built using the codular and airtable database. The expected outcome of this research activity is the application of new student registration at SMK Sinar Husni which can be used to solve problems that occur in the current registration system